(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
The objective of the article is to analyze results of quantitative data from academic productions that investigated xenophobia and related topics in the areas of communication sciences and that are available in open access in Brazilian and Portuguese online repositories. It is considered that open access online academic repositories constitute strategic spaces for scientific divulgation to academic communities, as well as to the general public. Xenophobia constitutes one of the greatest contemporary challenges to human rights, promoting exclusions and hierarchies that presuppose the superiority of some people over others. Data collection revealed that xenophobia is not necessarily addressed directly in the articles, dissertations, books and theses collected, and may appear from themes that are related to it.